Visual complex analysis - Needham, Tristan (Oxford University Press, 2023)
This new 25th anniversary edition of Visual Complex Analysis introduces this powerful method combining complex numbers with ordinary calculus, and includes new introductory content and brand-new captions that fully explain the geometrical reasoning.--